The impact of microbial phytase on the nutrition of monogastrics and the environment - Kemme P.A.; Jongbloed A.W.; van der Klis J.D. (Feed manufacturing in Southern Europe: New challenges, 1997)
In this paper the current status of knowledge on the impact of microbial phytases in pig and poultry production is reviewed, in relation to the environment. Firstly, information is given on the impact of legislation in the Netherlands, which focuses on P and N, with regard to livestock production and the environment. The mode of action of extrinsic phytases and an analytical method to measure their activity are reviewed. Supplementation of commercially available microbial phytases to diets for pigs and poultry results in enhancement of P digestibility/availability. In studies with pigs, the doses of microbial phytase (Natuphos) in the range of 500 to 2000 phytase units per kg of feed resulted in the generation of 0.8 to 1.0 g digestible P per kg of feed. In addition, the content of digestible calcium is increased, and amounts on average from 50 to 80 per cent of the increase of digestible P content. Soaking a phytate-rich diet or addition of lactic or formic acid to a diet with microbial phytase from Natuphos had a synergistic effect on the apparent digestibility of P and calcium. Up to 1.2 g of phytate P per kg of feed is limiting for a maximal effect of 450 phytase units per kg of feed. Performance (daily gain, feed conversion ratio) of pigs fed microbial phytase appears to be better as compared with a non-supplemented diet or with a positive control diet. Microbial phytase supplementation to diets for pigs and poultry can reduce substantially P excretion and, therefore, reduce environmental pollution.
South European Feed Manufacturers Conference, 1996/05/09-11, Reus (Spain)